PENCATATAN TRANSAKSI BISNIS SEDERHANA SEBAGAI SUMBER INFORMASI PADA USAHA KECIL DAN MENENGAH - Basuki Srihermanto (Sekolah Tinggi Ilmu Ekonomi AMM, 2018)
Efforts to increase the economy can be done, among others, by strengthening the positions and skills of small and medium businesses (SMEs), which is basically a part of development. Small and medium-sized industries have grown and grown rapidly over time. The rapid development of small and medium-sized industries has an impact on increasing competition. The purpose of this study is to analyze which SME groupings have been recording their business transactions and which have not done so. This research was conducted in small and winning industry in Bung Karno Pagutan Mataram, around campus STIA Mataram. By using survey method on the specified sample. While the data collection technique used is by using questionnaires, observation and interview techniques. The result of the research shows that almost all samples indicate that the business transaction record has not been done yet if there is still modest or very simple far from the rule of business transaction recording. This research is expected to provide information for stakeholder to be more concerned about SMEs for the progress of the business world in Indonesia